The Tenuipalpidae of Turkey, with a key to species (Acari: Trombidiformes) - Çobanoğlu, Sultan; Ueckermann, Edward Albert; Sağlam Hayri̇ye Di̇dem (Zootaxa, 2016)
A new Turkish species of Tenuipalpidae, Aegyptobia juniperi sp. nov., is described and seven previously recorded species are redescribed: Aegyptobia beglarovi Livshitz & Mitrofanov 1967, Brevipalpus rotai Castagnoli & Pegazzano, 1979, Cenopalpus bagdasariani (Livshitz & Mitrofanov, 1970), Cenopalpus bakeri Düzgüneş, 1967, Phytoptipalpus salicicola (Al-Gboory, 1987), Tenuipalpus granati Sayed, 1946 and Tenuipalpus punicae Pritchard & Baker, 1958. A key to the 28 species of Tenuipalpidae from Turkey is provided. Cenopalpus bagdasariani, B. rotai and A. beglarovi are new records for Turkey.